A colonizing attempt in Peru, 1835 - Cayo, Percy (1988)
​In this article the author presents a valuable document written by General Guillermo Milller about a journey he undertook to the east of Cusco in July 1835. From the author's point of view the document is especially noteworthy not only because of Miller's insights, but also because it reports one of the first attempts to colonize the Peruvian jungle in the early 19th century.